Epidemiological disaster management: Literature survey and analysis - Al-Husain, Raed (International Journal of Innovative Research and Scientific Studies, 2023)
Epidemiological disasters can cause significant suffering and change lives, but how they are handled can have just as much of an impact. This research aims to shed light on epidemiological disaster management literature from multidisciplinary perspectives and analyze its development and trends. A total of 365 scholarly articles were analyzed for this study using a number of databases from various academic disciplines. Search Keywords included “pandemic disaster management,” “pandemic planning,” “pandemic preparedness,” “pandemic response,” and “pandemic recovery.” Consequently, this paper surveys the literature and presents a brief background on epidemiological disasters and their management, a descriptive and inferential analysis of studies on the subject matter, a discussion of relevant issues, and suggested potential research directions for those interested. The analysis reveals that traditional methods for managing epidemiological disasters primarily rely on medical principles and policies, with medical sciences accounting for the great majority of studies, followed by social sciences. Moreover, the majority of the research has focused on response and preparedness, while recovery has gotten relatively little attention in favor of these earlier phases. Accordingly, based on various strategies/approaches exploited by different countries to deal with the COVID-19 pandemic and the trend of the existing body of research identified in this study, a paradigm shift in epidemiological disaster management is inevitable.